2017
DOI: 10.1093/mnras/stx448
|View full text |Cite
|
Sign up to set email alerts
|

Recurring OH Flares towards o Ceti: I. location and structure of the 1990s’ and 2010s’ events

Abstract: We present the analysis of the onset of the new 2010s' OH flaring event detected in the OH ground-state main line at 1665 MHz towards o Ceti and compare its characteristics with those of the 1990s' flaring event. This is based on a series of complementary single-dish and interferometric observations both in OH and H 2 O obtained with the Nançay Radio telescope (NRT), the Medicina and Effelsberg Telescopes, the European VLBI Network (EVN), and (e)Multi-Element Radio Linked Interferometer Network ((e)MERLIN). We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There are 3 recognised water maser superburst star forming regions (SFRs): Orion KL (Matveenko et al 1988;Garay et al 1989;Shimoikura et al 2005;Hirota et al 2011Hirota et al , 2014a, W49N (Honma et al 2004;Kramer et al 2018;Volvach et al 2019c) and G25.65+1.05 (Volvach et al 2017;Ashimbaeva et al 2017;Volvach et al 2019b). Sudden enhancement in maser flux density, though less extreme, has also been seen in species other than water (MacLeod et al 2018;Szymczak et al 2018) and in evolved stars (Esipov et al 1999;Vlemmings et al 2014;Gómez et al 2015;Etoka et al 2017).…”
Section: Introductionmentioning
confidence: 89%
“…There are 3 recognised water maser superburst star forming regions (SFRs): Orion KL (Matveenko et al 1988;Garay et al 1989;Shimoikura et al 2005;Hirota et al 2011Hirota et al , 2014a, W49N (Honma et al 2004;Kramer et al 2018;Volvach et al 2019c) and G25.65+1.05 (Volvach et al 2017;Ashimbaeva et al 2017;Volvach et al 2019b). Sudden enhancement in maser flux density, though less extreme, has also been seen in species other than water (MacLeod et al 2018;Szymczak et al 2018) and in evolved stars (Esipov et al 1999;Vlemmings et al 2014;Gómez et al 2015;Etoka et al 2017).…”
Section: Introductionmentioning
confidence: 89%
“…Variation of the IR pumping radiation has been linked, in at least some massive protostellar sources, to enhanced accretion events (Hunter et al 2019(Hunter et al , 2017. Most of the work described here relates to masers in star-forming regions, but we note that flaring variability in H2O (Brand et al 2018) and OH (Etoka & Le Squeren 1997;Etoka et al 2017) masers has also been observed in evolved stars, in addition to lower amplitude variations linked to the pulsation period, and associated stellar continuum variations, in these sources.…”
Section: Observational Backgroundmentioning
confidence: 50%
“…OH and water maser observations towards the Mira star o Ceti with the Nançay, Medicina and Effelsberg radio telescopes, in addition to MERLIN and EVN-(e)MERLIN, showed that the flaring regions are found to be less than 40±4 AU and, most unusually, the OH maser zone coincides with the water maser zone. The magnetic fields in the circumstellar envelope are found to be important, as can be seen from the highly ordered linear polarization vectors observed in the OH maser components of o Ceti [13].…”
Section: Masers In Evolved Starsmentioning
confidence: 83%